2020
DOI: 10.1164/rccm.201905-0996oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormones and Asthma in a Nationwide Study of U.S. Adults

Abstract: Rationale: Women have a higher burden of asthma than men. Although sex hormones may explain sex differences in asthma, their role is unclear.Objectives: To examine sex hormone levels and asthma in adults.Methods: Cross-sectional study of serum levels of free testosterone and estradiol and current asthma in 7,615 adults (3,953 men and 3,662 women) aged 18-79 years who participated in the 2013-2014 and 2015-2016 U.S. National Health and Nutrition Examination Survey. Logistic regression was used for the multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 32 publications
1
56
2
4
Order By: Relevance
“…In mouse models, DHT downregulated Th2 inflammation in the lung, but ARs enhanced such inflammation by upregulating M2 macrophage polarisation that induces eosinophil recruitment. 29 In our previous analysis in NHANES, in which there were both a LLOD and a broader range of serum estradiol levels than those in the current study, 10 we found no significant association between serum estradiol and asthma in our main analysis. Although our current finding of an association between a detectable serum estradiol and asthma and reduced FEV 1 /FVC in women, and reduced lung function measures (FEV 1 , FVC…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…In mouse models, DHT downregulated Th2 inflammation in the lung, but ARs enhanced such inflammation by upregulating M2 macrophage polarisation that induces eosinophil recruitment. 29 In our previous analysis in NHANES, in which there were both a LLOD and a broader range of serum estradiol levels than those in the current study, 10 we found no significant association between serum estradiol and asthma in our main analysis. Although our current finding of an association between a detectable serum estradiol and asthma and reduced FEV 1 /FVC in women, and reduced lung function measures (FEV 1 , FVC…”
Section: Discussioncontrasting
confidence: 75%
“…In our previous analysis of adults (ages 18 to 79 years) who participated in the US National Health and Nutrition Examination Survey (NHANES), we reported that higher levels of serum-free testosterone were associated with lower odds of current asthma in women but not in men. 10 Our finding of a significant inverse association between a high serumfree testosterone level and asthma among men in the current analysis is thus novel and likely due to greater statistical power, due to a much larger sample size in the UKB than in NHANES. 10 Alternatively, these results and our finding of no interaction between obesity and free testosterone in women with asthma in the UKB cohort could be explained by differences in the age range of participants in NHANES versus those in the UKB.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…On the other hand, high concentrations of testosterone and cyclic AMP in sputum of asthmatic women during the luteal phase of the menstrual cycle were thought to play a role in premenstrual exacerbations (43). The idea that sex hormones may be a causal factor in asthma was significantly strengthened by a recent study of 7,615 adults that quantified serum sex hormones and asthma outcomes (44). That study showed that low testosterone in both women and men was associated with an increased incidence of asthma.…”
Section: Asthmamentioning
confidence: 99%